Prediksi Pendapatan Sewa Dengan Data Mining Pada Perusahaan XYZ - Liana, May; Sanjaya, Christine; Widodo, Agus; Martinus, Marshall (Bina Nusantara University, 2010)
XYZ Company has a program to predict leasing income that only predict in constant condition where every tenant assumed for leasing renewal. This research is done to build accurate income prediction system that accommodate in making strategic decision towards the company. Premier data collecting is through direct interview with the company management. The analysis is through data training from the previous years to build neural network model. The analysis result shows that this model has produced error total value that is smaller than the previous error total value in years before. Therefore, it could be concluded that data mining with neural network technique that produced more accurate leasing income that could help the company making decision based on the hidden information in the database.